Antibodies to myelin oligodendrocyte glycoprotein in chronic relapsing inflammatory optic neuropathy. Issue 10 (4th December 2018) - Liu, Hongjuan; Zhou, Huanfen; Wang, Junqing; Xu, Quangang; Wei, Shihui
Abstract : Background/aims: To evaluate the status of myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) in chronic relapsing inflammatory optic neuropathy (CRION) and investigate its different clinical characteristics and prognosis. Methods: Patients diagnosed with CRION were recruited by the Neuro-ophthalmology Department of the Chinese People's Liberation Army General Hospital from December 2015 to April 2017. Based on antibody status, they were assigned to either the MOG-CRION or seronegative-CRION groups. Results: A total of 33 patients (38 eyes) were assessed and divided into the following groups: 22 (66.7%) MOG-CRION and 11 (33.3%) seronegative-CRION. The ratio of female to male was 1:1, and 81.8% of total CRION patients were adults (≥18 years). A total of 29 eyes (76.3%) showed severe visual loss (<20/200) during the first optic neuritis episode, and 37 eyes (72.5%) demonstrated good visual recovery (>20/40) during the final follow-up. The mean onset age of MOG-CRION patients was 28 ± 16 years (range 6–62), which was significantly younger than that of seronegative-CRION (45 ± 12 years, range 22–59) (p=0.029). The intraorbital and canalicular segments were highly involved in the orbital MRI of CRION patients. During the final follow-up, MOG-CRION patients had more bilateral involvement (p=0.008) and higher annualised relapse rates compared with the seronegative-CRION patients (p=0.019). Conclusion: CRION was predominantly found in adults with unilateral ON and exhibited a higher rate of seropositive MOG-IgG. MOG-CRION, which may be a disparate subtype of MOG-IgG-induced demyelinating disease that needs further investigation, was found in younger patients at onset, with more bilateral involvement and more relapse tendency.